Analisis Teori Konvergensi Media untuk Memahami Tranformasi Paradigma Komunikasi Massa dalam Era Digital : Pendekatan Studi Kepustakaan: A Literature Study Approach - Rozaq, Achmad Fatchur (representamen, 2025)
This research aims to analyze media communication paradigm transformation through media convergence theory approach and identify its implications for mass communication structure to develop integrative theoretical framework. Employing qualitative approach with systematic literature study method, analyzing relevant academic literature through content analysis and thematic analysis using media convergence theory framework. Findings identify five pillars of digital mass communication paradigm transformation: technological convergence, industry transformation, production democratization, consumption personalization, and algorithmic mediation that shifts communication structure from one-to-many to many-to-many with audiences as active prosumers. Media convergence theory successfully explains digital mass communication paradigm transformation and requires adaptation of classical mass communication theories in digital context. Produces new integrative theoretical framework serving as foundation for digital mass communication research and practical guide for contemporary media paradigm transformation.